Ethical dilemmas in geriatric nursing — selected issues - Zurzycka, Patrycja; Radzik, Teresa (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Due to the aging of modern societies, the care of the elderly is playing increasingly a more important role in health care. The provision of this care based upon medical knowledge entails also making reference to ethics. The specificity of old age diseases and the organization of benefits provided to senior citizens cause not only typical ethical dilemmas, but also specific problems determined by the needs and problems of elderly people. An essential issue in the nursing practice is the ability to recognize and to solve ethical dilemmas arising in their daily work. The settlement of emerging dilemmas should be based upon the established model of solving problems conditioned by respecting the rights of the patient and the action in the scope of the responsibilities and professional obligations within the principles of the effective law and ethics. The paper is aimed at showing the most frequent ethical dilemmas which will appear in connection with the care of the elderly and at showing a possible model to solve them.